Apalutamide plus Androgen Deprivation Therapy for Metastatic Castration-Sensitive Prostate Cancer: Analysis of Pain and Fatigue in the Phase 3 TITAN Study. Issue 4 (27th October 2021) - Agarwal, Neeraj; McQuarrie, Kelly; Bjartell, Anders; Chowdhury, Simon; Pereira de Santana Gomes, Andrea J.; Chung, Byung Ha; Özgüroğlu, Mustafa; Juárez Soto, Álvaro; Merseburger, Axel S.; Uemura, Hirotsugu; Ye, Dingwei; Given, Robert; et al.
Abstract : Purpose: We performed an exploratory analysis of prostate cancer-related pain and fatigue on health-related quality of life in patients with metastatic castration-sensitive prostate cancer receiving apalutamide (240 mg/day) or placebo, with continuous androgen deprivation therapy (ADT), in the phase 3, randomized, double-blind, placebo controlled TITAN trial (NCT02489318). Materials and Methods: Patient-reported outcomes for pain and fatigue were evaluated using the Brief Pain Inventory-Short Form and Brief Fatigue Inventory. Time to deterioration (TTD) was estimated by Kaplan-Meier method; hazard ratios and 95% confidence intervals were calculated using Cox proportional hazards model. General estimating equations for logistic regression estimated treatment-related differences in the likelihood of worsening pain or fatigue. Results: Compliance for completing the Brief Pain Inventory-Short Form and Brief Fatigue Inventory was high (96% to 97%) in the first year. Median followup times were similar between treatments (19 to 22 months). Median pain TTD was longer with apalutamide than placebo for "pain at its least in the last 24 hours" (28.7 vs 21.8 months, respectively; p=0.0146), "pain interfered with mood" (not estimable vs 22.4 months; p=0.0017), "pain interfered with walking ability" (28.7 vs 20.2 months; p=0.0027), "pain interfered with relations" (not estimable vs 23.0 months; p=0.0139) and "pain interfered with sleep" (28.7 vs 20.9 months; p=0.0167). Likelihood for fatigue and worsening fatigue were similar between groups. Conclusions: Patients with metastatic castration-sensitive prostate cancer receiving apalutamide plus ADT vs placebo plus ADT reported consistently favorable TTD of pain. No difference for change in fatigue was observed with apalutamide vs placebo.